2018
DOI: 10.1590/1516-4446-2017-2262
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral group therapy for intermittent explosive disorder: description and preliminary analysis

Abstract: This preliminary report is a significant addition to currently scarce clinical data. Our findings provide further evidence that structured cognitive-behavioral group therapy, with a focus on anger management and cognitive coping, may be a promising approach to the treatment of IED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
5
0
5
Order By: Relevance
“…While the limited empirical literature provides preliminary evidence of the potential differences between IED and NSSI, no direct investigation of the similarities and differences between IED and NSSI has been conducted. This is a gap in the literature since previous clinical trials have suggested that tailored treatments for specific subtypes of aggressive behaviors may increase treatment efficacy 13,14. For example, IED-focused cognitive-behavioral psychotherapy that specifically targets cognitive distortions and automatic thoughts related to IED, such as interpreting neutral stimuli as threats, as well as assertiveness training, appears to improve outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the limited empirical literature provides preliminary evidence of the potential differences between IED and NSSI, no direct investigation of the similarities and differences between IED and NSSI has been conducted. This is a gap in the literature since previous clinical trials have suggested that tailored treatments for specific subtypes of aggressive behaviors may increase treatment efficacy 13,14. For example, IED-focused cognitive-behavioral psychotherapy that specifically targets cognitive distortions and automatic thoughts related to IED, such as interpreting neutral stimuli as threats, as well as assertiveness training, appears to improve outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, IED-focused cognitive-behavioral psychotherapy that specifically targets cognitive distortions and automatic thoughts related to IED, such as interpreting neutral stimuli as threats, as well as assertiveness training, appears to improve outcomes. Unfortunately, tailored treatments for IED are scarce 13,14. Furthermore, tailored interventions targeting self-aggression (i.e., NSSI) are rare15,16 and are usually based on treatments for other disorders, including dialectic behavioral therapy, which was developed to treat borderline personality disorder 15…”
Section: Introductionmentioning
confidence: 99%
“…Por meio da psicoeducação, as intervenções informaram aos pacientes quanto à definição da raiva (processos psicológicos e bioquímicos), seus diferentes estilos e formas de expressão. Foram abordados também os riscos à saúde mental e cardiovascular, relações interpessoais e bem-estar físico global (Fernandez & Scott, 2009;Hesser et al, 2017;Costa et al, 2018). O monitoramento das emoções, identificação de gatilhos e o uso de técnicas de relaxamento também foram objetos de intervenções eficazes (Morland et al, 2010;Hutchinson et al, 2017).…”
Section: Discussionunclassified
“…Nesse contexto, embora a aceitação não tenha sido trabalhada de forma direta, constatou-se o uso de métodos para aumento da consciência emocional e corporal em intervenções bem-sucedidas de manejo da raiva, em especial nos estudos mais recentes (Yalcin et al, 2014;Walitzer et al, 2015;Aboulafia-Brakha & Ptak, 2016;Hesser et al, 2017;Costa et al, 2018). O princípio central por trás dessa abordagem é o desenvolvimento da automonitoração e da capacidade de raciocínio em meio ao sentimento, o que por sua vez contribui para o aprimoramento da capacidade do indivíduo de gerenciar o seu comportamento (Greenberg, 2012).…”
Section: Discussionunclassified
“…Although there is not currently an FDA approved treatment for violent individuals, psychotherapy, CBT, and anger management skills training are commonly used as treatment for intermittent explosive disorder and the other anger dependent disorders (Costa et al, 2018;McCloskey, 2019;McCloskey et al, 2008). CBT has shown effective reduction in rates of anger and recidivism in male offenders as well (Henwood et al, 2015).…”
Section: Misinterpretations and Angermentioning
confidence: 99%